Complex geophysical model of the Earth’s crust and upper mantle along the profile of RP-VI (Carpathians) - I. M. Logvinov; V. N. Tarasov; S. G. Slonitskaya; V. I. Tregubenko (Геофизический журнал, 2019)
A complex geophysical model is presented along the regional profile of RP-VI, which is located near the outlet to the terrestrial surface of the eastern boundary of the Skiba zone at its contact with, mainly, the Borislav-Pokuta zone of the Precarpathian trough. For the interpretation of magnetic data, the results of an aeromagnetic survey of a scale of 1 : 200 000 at a flight altitude of 2000 m were used, for the gravitational field — state gravimetric maps of the territory of the USSR in the Bouguer reduction of scale 1 : 200 000. For geoelectrical data, the magnetotelluric sounding curves obtained over the last 30 years have been used. Interpretation of gravimetric and magnetometric data was performed using the computer technology of data analysis KOSKAD3D, which is intended for analysis of three-dimensional digital geoinformation by the methods of a probabilistic-statistical approach. Interpretation of geoelectrical data is performed using the two-dimensional modeling program (inverse problem) — using the REBOCC algorithm. For the analysis of seismic data, the results of both the last century and the last decade are involved. The results of interpretation of different geophysical methods are presented in the form of vertical sections of physical parameters and their complex models of the earth’s crust and upper mantle to a depth of 90 km. The results of the geological and geophysical data presented in this paper differ from those obtained earlier by a new approach to the complex interpretation of potential fields and their comparison with previously unknown geoelectrical models. On the basis of the interpretation of potential fields, a peculiar element of the structure of the Earth’s crust was revealed, ap-parently connected with a sharp change in the composition of the rocks along the profile. The roof of this object undulates from the outlet to the surface at the northwest end of the profile to 25 km in its southeastern part. The sole of the layer from the end of the profile to the point 150 remains constant at a depth of about 25 km, drastically changing from 150 to the depths of the M boundary. It is shown that a sharp change in this object is accompanied by the presence of a low-resistance object that extends from 25 to 80 km with a maximum width of about 40 km. It is suggested that the position of this heterogeneity is related to the Tyachiv-Nadvornyansko-Monastyrtsky fault. The possible connection of a part of the selected element with oil and gas content is considered.